Soil Degradable Bioplastics for a Sustainable Modern Agriculture - Malinconico, Mario (Green Chemistry and Sustainable Technology,, 2017)
This book shows how the use of biodegradable plastics in agriculture may exert a profound positive impact in the plasticulture. Starting from the organic chemistry approach to biodegradable and compostable plastics, either natural or synthetic, the book analyzes the huge area of existing bioplastics for protected cultivation (mulching, direct cover, low tunnels) from technological as well as agronomic approaches. The book then describes recent results of a new approach, sprayable biodegradable mulching, which resides on the use of waterborne polysaccharides and cellulosic fibers. A further chapter describes the research and technology of biodegradable plastics for different agricultural practices. A chapter on Life cycle assessment (LCA) of biodegradable plastics for agriculture, and one on existing and developing normative in the field complete the book. This book is then useful to agronomists, chemical and materials engineers, polymer technologists and scientists, as well as to a more general audience of educated people who are interested in the application of green chemistry principles to the vast world of crop production. Mario Malinconico is Research Director at the Institute of Polymers, Composites and Biomaterials of National Research Council, Italy.